Meeting the Contraceptive Needs of Key Populations Affected by HIV in Asia: An Unfinished Agenda - Tricia Petruney; Shanthi Noriega Minichiello; Misti McDowell; Rose Wilcher (AIDS Research and Treatment)
Like all women, women living with and at risk of acquiring HIV have the right to determine the number and timing of their pregnancies and to safely achieve their reproductive intentions. Yet, many women in Asia affected by HIV lack access to family planning services and experience disproportionately high rates of unintended pregnancy and abortion. Programs that have succeeded in promoting condom use and providing HIV prevention and treatment services in this region have largely missed the opportunity to address the contraceptive needs of the key populations they serve. The importance of better linkages between family planning and HIV policies and programs is now widely recognized by global health policymakers and donors. However, to date, most of the efforts to improve these linkages have been conducted in Africa. Greater attention is needed to the developing, implementing, and evaluating of integrated family planning/HIV approaches that are tailored to the political, cultural, and public health context in Asia. In this paper, we describe the use of and need for family planning among key populations affected by HIV in Asia, discuss the challenges to effectively addressing of these needs, and offer recommendations for strengthening the linkages between family planning and HIV policies and programs in the region.